EFEKTIVITAS MEDIA BARU DALAM SOSIALISASI PROGRAM LAWAN HOAX SAAT PANDEMI COVID-19 DI DINAS KOMUNIKASI DAN INFORMATIKA KOTA PALANGKA RAYA - Junaidi, Junaidi; Anggraini, Dian Zannuba (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Covid-19 became the largest non-natural disaster outbreak in the world in 2020. This virus first spread to other countries, including Indonesia. The public is in uncertainty in receiving a lot of information about Covid-19 in various mass media, including social networks. This condition is exacerbated by fabricated news to cover up actual information related to Covid-19 which is difficult to contain. This study aims to get an overview of community behavior related to the spread of the Covid-19 hoax. The results of the study concluded that knowledge about Covid-19 and hoaxes was very adequate. However, most of those interviewed were hesitant in distinguishing hoax news or not. This is because of the large amount of information they receive every day. Public panic over Covid-19 has led to the continued spread of hoaxes in the hope that this information can be useful in preventing and treating regardless of the truth. Meanwhile, most people have not been able to identify with certainty about the Covid-19 hoax. so, some of them are hesitant to spread the news. because they consider that the information is not valid or the truth is known, because the news may be considered detrimental or of importance to several parties.